Morbidity and Mortality Pattern of Neonates Admitted to Neonatal Care Unit.Central Teaching Pediatric Hospital Baghdad - Ibrahim, Riyadh M (AL-Kindy College Medical Journal, 2020)
Background; Neonatal period is a very vulnerable period of life due to many problems, In spite of advances in perinatal and neonatal care still, the mortality rate of neonate high especially in developing country The World Health Organization estimates that globally four million neonatal deaths per year, Developing countries account for around 99% of the neonatal mortality in the world, In Iraq. Neonatal mortality rate about 19 per 1000 live births which represent 56% of child death below 5 years age in 2012. . Objectives The aims of the study were to determine the institutional new-born case fatality rate and the cause of admission and death in the neonatal care unit. Method; Across-section study was carried out of the Neonatal Care Unit of Central Teaching Hospital of Pediatric in Baghdad Al-krakh Health Directorate Result; During 2015, 1977 neonates were admitted, Mortality rate was 9%, Four main causes of death were identified; Respiratory related condition, Bacterial sepsis, premature neonate (Disorder related to short gestational and low birth weight not relayed to elsewhere classification) and congenital malformation 37.5%, 33.3%, 7.1% and 7.1% respectively , The main causes of morbidity were Neonatal jaundice, Respiratory related condition, Bacterial sepsis 37.5%, 35.2%. 14.1% respectively Conclusions: The majority of neonatal morbidity and mortality can be prevented by appropriate interventions